Security of Digital Signature in E-commerce using Elliptic Curve Cryptography - Dhillon, tamkaur Singh; Kaur, Ms.; Kumar, nagesh (Gyan Management Journal, 2010)
paper the researchers have designed an elliptic curve digital signature algorithm that provides the same and security as the standard digital signature algorithm, but delivers it in a smaller key size. In : : ::jon, less storage, lesspower and less memory is provided than other systems and make it possible to."ement cryptography in many special platforms such as wireless devices, laptop Computers and smart